Sistem Monitoring Gudang Dengan Sensor Ultrasonik Berbasis Microcontroller Arduino Pada PT XYZ - Warsino Nardiwiyono; Anus Wuryanto; Cepi Cahyadi (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2022)
The rapid advancement of technology provides convenience for humans. The presence of the internet of thinks (IoT), is able to solve problems related to warehouse security. This study aims to be able to control warehouse security in real time remotely by utilizing SMS notification messages on mobile phones. Applying the prototyping research method, this research on warehouse monitoring systems with ultrasonic sensors based on the Arduino microcontroller is able to produce system security by providing hazard warning messages to warehouse supervisors. So that incidents of theft can be detected in a fast time.